Frequency and Severity of COPD in Smokers (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency and severity of COPD in smokers working at Services Hospital/SIMS, Lahore by using spirometry. Study design: Cross-sectional survey. Subjects & methodology: This study was conducted at Department of Pulmonology, Services Hospital, Lahore from July 2010 to February 2011. Total 100 cases (Doctors/paramedical staff working in Services Hospital, Lahore were included in this study. Patients were labeled as having COPD if FEV1 /FVC 80%), moderate (FEV1 80-50%), severe (FEV1 50-30%), very severe (FEV1
Keywords: Nasal endoscope, COPD, smokers, FEV1, FVC.